Educational Process In Preparing Students For Professional Activity (Eurasian Journal of Learning and Academic Teaching, 2024)
The article explains that the pedagogical process mainly includes two active features, systematic approach to self-development of students and comprehensive development of personality. In modern conditions, the concept of "technology" acquires a new meaning in the theory and practice of pedagogy